Ethnic origin of Israeli Jews and psychological responses to the extreme stress of the ongoing war with Hamas in Gaza - Eshel, Yohanan; Kimhi, Shaul; Marciano, Hadas; Adini, Bruria (Frontiers in Psychology, 2024)
Introduction Discrimination constitutes a source of stress for minority groups, leading to heightened levels of depression. Discrimination can also elicit positive responses aimed at reducing detrimental impacts. The stress experienced by minority groups may impact their mindset and influence their negative emotional responses. Israeli Jewish society comprised for many years two large communities: the dominant Ashkenazi people, who emigrated from East Europe, and the Mizrahi discriminated minority whose members came from Muslim countries. The Mizrahi minority has become a mainstream community over time, and its size equals the Ashkenazi group. This change raises an interesting issue that has not been investigated empirically: What characterizes the psychological responses to the stress of a formerly discriminated minority? Methods Two representative samples responded to a similar questionnaire measuring inhibiting and bolstering coping strategies. The first sample of 930 people participated in this structured survey between October 12 and 19, 2022. No external adversity threatened Israel at that time. The second sample of 1,608 Israeli Jews participated between October 11 and 17, 2023, a few days after Hamas attacked the southern region of Israel, killed more than a 1,000 people, and kidnapped 100. We examine the impact of moderate and extreme stress of war on the maladaptive levels of anxiety and depression. Furthermore, we investigated the shielding psychological coping measures of this former minority, as compared to Ashkenazi group’s response. Results Results show that the formerly minority Mizrahi group expresses higher levels of depression, anxiety, and sense of danger under extreme stress compared to the Ashkenazi group. Mizrahi individuals compensated concurrently for these negative emotions by fostering enhanced hope and societal resilience compared to the other group. Discussion The main contributions of the present study are (a) Demonstration that psychological responses of descendants of a minority group to highly stressful conditions do not necessarily agree with their current status as a mainstream community. (b) Indicating that the phenomenon of concurrently enhanced negative and positive responses in face of extreme stress is associated with ethnic origin and history. (c) Associating the effects of different socio-demographic variables with the psychological response of the investigated groups to extreme and moderate stress.